Information literacy in portuguese school libraries: a longitudinal study of master degree dissertations - Novo, Ana (2019)
Since the beginning of the 21st century, a rapid growth in access to information and communication technologies has been observed in Portugal, as well as in other European countries. School libraries (SL) and teacher librarians (TL) play a fundamental role as they have been increasingly considered by school communities as an essential resource for developing information literacy (IL) competences. The methodology for this study was a meta-analysis of the results of a body of master dissertations, completed between 2007 and 2017, at Universidade Aberta, Portugal. A first group of the analysed dissertations indicated that in general, TL misunderstood the concept of IL, were still not aware of its importance and most of their work was still related to traditional library activities. In more recent years we have identified some important improvements in Portuguese SL and in research studies and evidence of that progress is shown.